2/3(6x-9)=4x-6

Simple and best practice solution for 2/3(6x-9)=4x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2/3(6x-9)=4x-6 equation:



2/3(6x-9)=4x-6
We move all terms to the left:
2/3(6x-9)-(4x-6)=0
Domain of the equation: 3(6x-9)!=0
x∈R
We get rid of parentheses
2/3(6x-9)-4x+6=0
We multiply all the terms by the denominator
-4x*3(6x-9)+6*3(6x-9)+2=0
Wy multiply elements
-12x^2(6+18x(6+2=0

See similar equations:

| 5(2x–3)=7x+3 | | 7x+5=3x+13C | | 8−2m=2 | | 15p-9p-p+4p=18 | | O.375c-11=13 | | -2x^2(x+46x(x+1=0 | | 7x+5=2(4x=3) | | 4a+2a-3a=18 | | 13x-3=10x=6 | | 2x+40+(x-10)=180 | | 5x+7+3x=−8+3x​ | | y=-2y+9 | | .5x+15=90 | | 6(n+3)=4(3n+3) | | y/4-6=10 | | 2h–14=2 | | 3n²=0 | | 2x+22+5x-17+x=180 | | 5t^2+30t-45=0 | | 4/5x+3=-1/4x-1= | | 11p^2+7p-16=0 | | (x*x)+5x−66=0 | | 12d+-10d=14 | | w=3w+1+w | | 2=0.5(5x-8) | | 54=9*x | | 4p÷4-2p÷3=10 | | t÷5-8=12 | | 4x-25)+75=180 | | 3s+4=8 | | 2(3x–5)4x+6=0 | | 3(x+6=-27) |

Equations solver categories